The Persian soccer spectator behaviour inventory (PSSBI): Development and psychometric properties of the PSSBI using structural equation modelling (SEM) - Nemati, Nematallah; Ostovar, Shahla; Griffiths, Mark Damian; Md Nor, Mariani; Ramayah, Thurasamy (Universiti Putra Malaysia, 2018)
Psychometric instruments assessing spectator motives for attending professional sports have mostly been validated in a Western context. The present study describes the development of the Persian Soccer Spectator Behaviour Inventory (PSSBI). The 21-item PSSBI was completed by 1385 Iranian spectators. Exploratory factor analysis indicated that the 21 items loaded on four factors: Promotional Incentives, Game Attractiveness, Schedule Considerations, and Economic Considerations. These factors demonstrated acceptable internal consistency and explained 65.48% of the total variance. It is concluded that the resulting 20-item PSSBI is a viable tool for assessing football fans’ motives for attending professional football matches in Iran.